Anticonvulsant Activities of Asperphenamate and Nepetaefuran Isolated from Leucas martinicensis (Jacq.) Ait. f. - Bodrix, Noudou Solitaire; Armand, Malle Lando; Celine, Mbazoa Djama; Godfred, Aponglen Ayimele; Jean, Wandji; Germain, Taiwe Sotoing; Dereck, Ndinteh Tantoh; Rostan, Talla Mangoua (Sciences of Phytochemistry, 2026)
A known peptide, Asperphenamate (1) and a labdane diterpenoid, Nepetaefuran (2) were isolated for the first time from the aerial parts of Leucas martinicensis (Jacq.) Ait. f. (Lamiaceae) together with five known compounds: ß-sitosterol-3-O-ß-D-glucopyranoside and β-sitosterol, oleanolic acid and ursolic acid and Apegenin-7-O-glycoside. The structures of these compounds were established on the basis of mass spectrometry, NMR data and by the comparison with literature data. The dichloromethane-methanol (1:1, v/v) (LM) extract, the peptide and the labdane diterpenoid compounds were evaluated for their anticonvulsant effects on pentylenetetrazol, picrotoxin or bicuculine induced convulsions in mice. All the tested treatments showed anticonvulsant effects on experimental models of epileptic seizures chemically induced in mice. Asperphenamate (1) (JW514) showed up to 100% protection of animals against convulsions, Nepetaefuran (2) (JW512) and the dichloromethane-methanol (1:1, v/v) (LM) extract showed a maximum of 83.33% protection against pentylenetetrazol induced convulsions.